2020
DOI: 10.3390/jcm9113672
|View full text |Cite
|
Sign up to set email alerts
|

Glycation Increases the Risk of Microbial Traversal through an Endothelial Model of the Human Blood-Brain Barrier after Use of Anesthetics

Abstract: The function of the human blood–brain barrier (BBB), consisting mainly of the basement membrane and microvascular endothelial cells, is to protect the brain and regulate its metabolism. Dysfunction of the BBB can lead to increased permeability, which can be linked with several pathologies, including meningitis, sepsis, and postoperative delirium. Advanced glycation end products (AGE) are non-enzymatic, posttranslational modifications of proteins, which can affect their function. Increased AGE levels are strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…MGO also induced reactive oxygen species (ROS) formation [23,24], blood-brain barrier (BBB) hyperpermeability [25,26], chromatin condensation, and ER stress [27,28], as shown in previous studies.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…MGO also induced reactive oxygen species (ROS) formation [23,24], blood-brain barrier (BBB) hyperpermeability [25,26], chromatin condensation, and ER stress [27,28], as shown in previous studies.…”
Section: Discussionsupporting
confidence: 72%
“…MGO was cytotoxic (2 mM) in our cerebral endothelial cell model and, previously, was also shown to be cytotoxic in different cell lines including neuroglial cells, HUVECs, and human brain endothelial cells [ 7 , 21 , 22 ]. MGO also induced reactive oxygen species (ROS) formation [ 23 , 24 ], blood–brain barrier (BBB) hyperpermeability [ 25 , 26 ], chromatin condensation, and ER stress [ 27 , 28 ], as shown in previous studies.…”
Section: Discussionmentioning
confidence: 73%
“…Before studying the permeability of the BBB after application of propofol, we analyzed the cell viability of THBMEC cells in the presence of propofol with 3 µg/mL, which is a commonly used concentration in surgery, and found that the cell viability was not affected by propofol (data not shown and in [ 22 ]). The effect of propofol on the permeability of THBMECs was further analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…There exist several studies indicating that anesthesia can affect the BBB. One particular example we previously investigated was the non-volatile anesthetic propofol [ 22 ]. Propofol is a phenolic derivative and is considered one of the more favorable intravenous anesthetics due to its rapid onset of effect, short plasma half-life and its low accumulation in tissues [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The blood-brain barrier (BBB) is the endothelial cell layer of the brain that separates the brain from the blood. It regulates the exchange of drug-like compounds between blood and brain 41 . The ability of the identified compounds to permeate through BBB was predicted and the results are illustrated in Table 5.…”
Section: Solubility Propertiesmentioning
confidence: 99%